The effect of temperature and nitrogen source modulation on Pseudomonas fluorescens AQP671 ice recrystallization inhibition activity - Õnnela Luhila; Ildar Nisamedtinov; Toomas Paalme; Katrin Laos; Allan Olspert (PLoS ONE, 2025)
Cold-adapted organisms have developed many different mechanisms to protect themselves from freezing temperatures. One of these mechanisms is ice recrystallization inhibition (IRI) activity. IRI refers to the ability of certain proteins and compounds to prevent the growth of ice crystals during freeze–thaw processes. The IRI activity of Pseudomonas fluorescens AQP 671 culture media was evaluated in relation to various nitrogen sources, incubation temperatures and pH conditions. The highest IRI activities were achieved with amino acids L-asparagine, L-proline, or L-valine, particularly under prolonged low-temperature cultivation. A rapid increase in IRI activity was observed during the first 24 hours, in response to cold shock, correlating with cell density. The activity was detected at temperatures below 15 °C, with the highest IRI activities achieved at 5–10 °C. The optimal pH range for high IRI activity was pH 6–8, and it was negatively affected by low (2–4) and high (10–12) pH values. These findings highlight the importance of both environmental conditions and nutrient composition in the expression of IRI activity in Pseudomonas fluorescens AQP671 culture media.